PERFORATION OF SMALL INTESTINE IN PREMATURE NEONATE - POSTOPERATIVE MANAGEMENT CASE REPORT - Naunova Timovska, Silvana; Mandzukovska, Hristina; Martinovska, Iskra; Atanasova, Olgica; Kraljeva, Eva (Journal of Morphological Sciences, 2025)
Gastrointestinal perforation (GIP) in neonates is a severe, acute, life-threatening condition associated with multiple complications and a high mortality rate. It is most often associated with necrotizing enterocolitis, but it also often occurs spontaneously due to local intestinal ischemia. Early detection and timely surgical intervention, with appropriate respiratory support and individualized nutritional support, are crucial in the outcome and survival of extremely premature neonates. We present a case of postoperative management of an extremely premature infant from a twin pregnancy after surgical intervention due to intestinal perforation. Keywords: premature neonate, spontaneous gastrointestinal perforation, necrotizing enterocolitis